Hearing Profile of Brazilian Forestry Workers' Noise Exposure - Lacerda,Adriana (2015)
Introduction Researchers studying the hearing health of forestry workers have revealed the presence of a noise-induced hearing loss (NIHL) in this population and have concluded that the vibration of the equipment, the carbon monoxide released by motors, and pesticides might also contribute to NIHL. Objective To analyze the noise exposure in the Brazilian forestry industry workers and the effects on hearing. Methods The study sample comprised 109 employees of a company that specialized in reforestation. Their participants' mean age was 35.5 years (21 to 54 years), mean tenure at the company was 3.9 years (1 to 13 years), and mean total duration of noise exposure was 12.3 years (1 to 30 years). The existing documentation reporting on the jobs risk analysis was examined, noise level was measured, and pure tone audiometry was performed in all participants. Participants were divided into three groups according to their noise exposure levels in their current job. Results Of the participants who were exposed to noise levels less than 85 dBA (decibels with A-weighting filter), 23.8% had hearing loss, and 5.5% of the participants who were exposed to noise ranging from 85 to 89.9 dBA and 11% of the participants who were exposed to noise greater than 90 dBA had audiogram results suggestive of NIHL. Conclusion The implementation of a hearing loss prevention program tailored to forestry workers is needed.